Fra stormflodsflygtning til erhvervsmigrant. Mobilitet fra Limfjordstangen 1825-1910’erne - Gardiner, Jake Hubert; Knudsen, Inger Bjørn; Knudsen, Line Vestergaard (Historisk Tidsskrift, 2023)
From Flood Refugee to Opportunistic Migrant: Mobility from an Exposed Coastal Area, 1825–1915 This article investigates mobility patterns from a coastal area exposed to changing and challenging environmental conditions by identifying the driving forces behind three waves of relocations from Limfjordstangen (an isthmus on the West coast of Denmark) between 1825 and 1915. Inspired by contemporary migration studies, narratives that analytically illuminate the numerous and mutually related driving forces of mobility are woven from records of valuations of the victims’ losses, descriptions and reports from the local administration, the arrival and departure lists of the church registers, and contemporary descriptions of topographical conditions on Limfjordstangen. Throughout the studied period, mobility was characterized by group moves. The mobility patterns away from the isthmus were first motivated by floods that put pressure on the population’s housing and land properties. However, the last of the three relocation waves was characterized by families migrating to optimize fishing and earning opportunities. We thus conclude that there is a change from relocations forced by natural disasters to more planned, well-considered and profit-seeking relocations. The article discusses this change in mobility pattern as part of an emerging modernization at the isthmus and considers the possibility that a special local tendency to migrate occurred in the area during the late 1800s.